2019
DOI: 10.1002/cam4.1940
|View full text |Cite
|
Sign up to set email alerts
|

Desmoplastic small round cell tumors: Multimodality treatment and new risk factors

Abstract: Background To evaluate optimal therapy and potential risk factors. Methods Data of DSRCT patients <40 years treated in prospective CWS trials 1997‐2015 were analyzed. Results Median age of 60 patients was 14.5 years. Male:female ratio was 4:1. Tumors were abdominal/retroperitoneal in 56/60 (93%). 6/60 (10%) presented with a localized mass, 16/60 (27%) regionally disseminated nodes, and 38/60 (63%) with extraperitoneal metastases. At diagnosis, 23/60 (38%) patients had effusions, 4/60 (7%) a thrombosis, and 37/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(64 citation statements)
references
References 63 publications
3
55
0
2
Order By: Relevance
“…Last, in patients with desmoplastic small round-cell tumors, MC was associated with more frequent complete remission and longer event-free survival. 27…”
Section: Discussionmentioning
confidence: 99%
“…Last, in patients with desmoplastic small round-cell tumors, MC was associated with more frequent complete remission and longer event-free survival. 27…”
Section: Discussionmentioning
confidence: 99%
“…Recientes estudios comparativos plantean un esquema menos tóxico y tan beneficioso como el anterior: VAIA (ifosfamida, vincristina, adriamicina D, carboplatino y actinomicina D). 19 Un esquema de citorreducción más quimioterapia intraperitoneal hipertérmica (CRS/HIPEC) se vislumbra como una opción terapéutica con morbilidad periope ratoria aceptable. Sin embargo, el impacto a largo plazo sigue siendo mal definido.…”
Section: Discussionunclassified
“…The authors concluded that high-dose chemotherapy probably has no role in the treatment of DSRCT [ 51 ]. More recently, Scheer et al [ 52 ] found that patients treated with the VAIA regimen (ifosfamide, vincristine, doxorubicin, actinomycin D) presented longer event-free survival (29.4 months) compared to other protocols, including the P6 protocol. The interval-compressed regimen of vincristine, irinotecan, temozolamide (VIT) was evaluated in 6 pediatric patients and showed a tolerable profile with an objective response rate of 50% to the first 2 cycles of VIT [ 53 ].…”
Section: Treatmentmentioning
confidence: 99%